Evaluating the hazards of background radiation and cesium in the soil of greenhouses within the region of Riyadh, Saudi Arabia - Aboukarima, Abdulwahed Mohamed; Tabash, Ibrahim Soliman; bin Muhaiza, Abdulmajeed Mohammed; Alqahtani, Mohammed Saleh; Salman, Tawfiq Ahmed (Journal of agricultural, environmental and veterinary sciences, 2020)
The study evaluates the hazards of background radiation and Cesium- 137 in the soil of greenhouses within the region of Riyadh, Saudi Arabia. The Mole detector was utilized. It renders readings for the concentration of Uranium- 238, Thorium- 232, Potassium- 40 and Cesium- 137. Field measures were conducted at Alkharj at Nowara Farm Nurseries, Saudi Arabia. Measures were taken at three different greenhouses (plastic covered, glass covered and fiber glass covered). The plants at the plastic- covered greenhouse were cucumber, pepper and eggplant while in the glass and fiber glass- covered greenhouse, the vegetation were ornamental plants and flowers. The average concentration of Uranium- 238 recorded (19.33 Bq/ kg), Thorium- 232 (14.09 Bq/ kg), Potassium- 40 (130.77 Bq/ kg) and Cesium- 137 (1.81 Bq/ kg). These values are less than the world rates. Some radiation hazard indices were also calculated like Radium Equivalent (Raeq), the absorbed dose of Gamma rays in the air, external and internal hazard indices with the purpose of evaluating the dangers of the radiations existing in the greenhouse soil on health. The average radium equivalent activity (Raeq) recorded (49.56 Bq/ kg) which is less than the permissible world rates (370 Bq/ kg). The absorbed dose of Gamma rays in the air recorded (22.94 nGy/ hr) which is again less than the permissible world rates (59 nGy/ h). The average internal and external hazard indices recorded less than one and came within the world permissible limits.
Keywords: Background Radioactivity; greenhouses; soil; Mole detector